Clinical efficacy of chlorhexidine chips and tetracycline fibers as an adjunct to non surgical periodontal therapy - Singh, Munishwar; Shreehari, A. K.; Garg, P. K.; Singh, Sangeeta (European Journal of General Dentistry, 2014)
Context: Local drug delivery agents. Aims: To clinically evaluate the efficacy of Chlorhexidine chip (PerioCol™ CG) with Tetracycline fibers (Periodontal Plus AB™). Settings and Design: Randomized controlled, split mouth study design with an observation period of six months. Materials and Methods: Patients were allocated in 3 experimental treatment groups, Group A: SRP + CHX Chip, Group B: SRP + Tetracycline fibers, and Group C: SRP alone (control group). 420 bleeding sites in 35 patients (18 females and 17 males) with chronic periodontitis (5-8mm probing depth), were evaluated clinically for pocket probing depth (PD), Clinical Attachment level (CAL), and Bleeding on Probing (BoP). Statistical Analysis:T-test and CV. Results: All the treatment groups were found to be efficacious as demonstrated by improvement in PD, CAL, and BoP. In the short term, CHX group showed increased gain of CAL but on long term observation the Tetracycline fiber group showed better consistent clinical results in comparison to the other two groups. Conclusions: Group B (SRP + Tetracycline fibers) resulted in better optimum clinical results in comparison to the other two treatment groups.
Keywords: Chlorhexidine chips; chronic periodontitis; local drug delivery; periodontal pocket; tetracycline fibers